Anti-cancer activity of grape seed semi-polar extracts in human mesothelioma cell lines - Francesco Di Meo; Riccardo Aversano; Gianfranco Diretto; Olivia Costantina Demurtas; Clizia Villano; Salvatore Cozzolino; Stefania Filosa; Domenico Carputo; Stefania Crispi (Journal of Functional Foods, 2019)
Malignant mesothelioma is a tumor that affects pleural surface and has very poor prognosis. The standard therapeutic modalities for this cancer have yielded unsatisfactory outcomes, therefore the development of alternative and effective therapies is currently an urgent requirement.Grapevine is a plant rich of bioactive compounds, known for its therapeutic effects. Here, we describe the anti-cancer activity of grape seeds semi-polar extracts of two Italian grape varieties (Aglianico and Falanghina) in mesothelioma in vitro. Seed extracts from both varieties induced intrinsic apoptosis in a dose and time-dependent manner in three different human mesothelioma cell lines. Global metabolic analysis of this fraction revealed a higher accumulation of phenylpropanoid precursors and proanthocyanidins and expression of genes involved in the aforementioned pathways.These findings suggest that new phenolic molecules from grape seeds could be viewed as new drugs to be used alone or in combinations with standard chemotherapeutics in mesothelioma treatment.